Atypical pathogens associated with cardiac implantable electronic device infections. Issue 9 (26th July 2021) - Kohli, Utkarsh; Hazra, Aniruddha; Shahab, Ahmed; Beaser, Andrew D.; Aziz, Zaid A.; Upadhyay, Gaurav A.; Ozcan, Cevher; Tung, Roderick; Nayak, Hemal M.
Abstract: Background: Cardiovascular implantable electronic device (CIED) infections are associated with significant morbidity and mortality making the identification of the causative organism critical. The vast majority of CIED infections are caused by Staphylococcal species. CIED infections associated with atypical pathogens are rare and have not been systematically investigated. The objective of this study is to characterize the clinical course, management and outcome in patients with CIED infection secondary to atypical pathogens. Methods: Medical records of all patients who underwent CIED system extraction at the University of Chicago Medical Center between January 2010 and November 2020 were retrospectively reviewed to identify patients with CIED infection. Demographic, clinical, infection‐related and outcome data were collected. CIED infections were divided into typical and atypical groups based on the pathogens isolated. Results: Among 356 CIED extraction procedures, 130 (37%) were performed for CIED infection. Atypical pathogens were found in 5.4% (n = 7) and included Pantoea species (n = 2), Kocuria species (n = 1), Cutibacterium acnes (n = 1), Corynebacterium tuberculostearicum (n = 1), Corynebacterium striatum (n = 1), Stenotrophomonas maltophilia (n = 1), and Pseudozyma ahidis (n = 1). All patients with atypical CIED infections were successfully treated with total system removal and tailored antibiotic therapy. There were no infection‐related deaths. Conclusions: CIED infections with atypical pathogens were rare and associated with good outcome if diagnosed early and treated with total system removal and tailored antimicrobial therapy. Atypical pathogens cultured from blood, tissue or hardware in patients with CIED infection should be considered pathogens and not contaminants.